ASSISTED GEOGRAPHICAL DIALOGUE: ADAPTING THE AI POWERED NARRATIVE CO DESIGN METHOD TO SECONDARY HISTORY AND GEOGRAPHY TEACHING - Moreno, Carlos Guallart (Seven Editora, 2025)
This article proposes a didactic adaptation of the narrative co design method with artificial intelligence (AI) for teaching History and Geography in the third year of Spanish secondary education. After a critical reflection on how to interact with generative AI, the paper contrasts the direct integration approach—asking AI follow up questions after studying a topic—with the alternative of narrative co design, in which teachers and students play an active, creative role. The process begins with a factual analysis of a real case (Case A) via AI prompts. The teacher then writes a reflective piece linking the case to a curriculum concept (Theme 1). A narrative exploration phase follows, where simulated voices—such as protagonists, antagonists or experts—enrich the dialogue. Finally, the AI synthesises the discussion and students debate and evaluate the proposals, thus developing spatial competence and critical thinking. The article concludes that this methodology turns AI into a cognitive mediator, encourages student participation and creativity, and provides a flexible model for addressing contemporary issues through Geography and History. DOI: https://doi.org/10.56238/sevened2025.030-046